NON-CONTRIBUTORY SOCIAL SECURITY APPLICATION FOR ELDERLY AND INDIVIDUALS WITH DISABILITIES’: THE CASE OF TURKEY - Mete Kaan Namal; Aynur Yumurtacı; Bülent Arpat (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
In Turkey, although the social security of the disadvantaged, elderly and/or individuals with disabilities take place within the non-contributory system and them having the same requirements to claim their monthly payments, the amount of individuals with disabilities’ Monthly Payments which were paid until June 2018 have always exceeded the Elderly Persons’ Monthly Premiums. In contrast, afterwards the 2016 amendment, the individuals with disabilities have faced injustice with the “per capita income” principle, which was implemented in favor of the elderly. With this study, we aim to emphasize that with the adoption of the Individuals with Disabilities' Law of 2005, the conditions and amount of premiums to claim Elderly and Individuals with Disabilities’ Monthly Benefits are inconsistent with the social justice principle. Thus, we state that the amount of monthly payments paid to the disadvantaged elderly people and individuals with disabilities are insufficient to have them reach the minimum living standards. Accordingly, it became evident that to fulfill the social justice principle in paying the elderly and individuals with disabilities’ monthly premiums within the non-contributory system in Turkey, indexation has to be carried at 40% rate of the “per capita net income”.